Analisis Pengaruh Kualitas Website Kejaksaan Negeri Penajam Paser Utara Menggunakan Metode Webqual - Nurul Saqa Aqmarina; Dila Seltika Canta; Nuorma Wahyuni; Erlin Setyaningsih; Adi Hermawansyah; Sudarman Sudarman (STMIK Budi Darma, 2022)
The information technology that used by the Penajam Paser Utara Regency of Prosecuting Attorney Office is a website to support information and public services is more easily, on the website there are several news` menus, profiles, vision and mission, and several of public services. The main function of the Penajam Paser Utara regency of Prosecuting Attorney website as an online public service facility. So far the Penajam Paser Utara Regency prosecuting Attorney has paid little attention to their website and there has no progress because the Penajam Paser Utara Regency of Prosecuting Attorney has no permanent staff in the Information Technology section .The purpose of this research is to know how the quality of the Penajam Paser Utara Regency Prosecuting Attorney Office website affects To The user satisfaction based on the WebQual 4.0 method. The results of the Research for usability quality (X1), it can be seen that the significance value of the usability quality (X1) is 0.035 < 0.05 or T count 2.143) > T table (1.995) so H1 is accepted, then there is an influence between the usability quality (X1) with the user satisfaction (Y). Meanwhile, for Information Quality (X2), it can be seen that the significant value of the information quality (X2) is 0.064 > 0.05 or T count (-1.878) < T table (1.995) so H2 is rejected, so there is no influence between the information quality (X2) with the satisfaction user (Y). As for the Quality of Interaction (X3), it can be seen that the significance value of the quality of the interaction (X3) is 0.002 <0.05 or T count (3.184) > T table (1.995) so H3 is accepted, then there is an influence between the quality of the interaction (X3) with The user satisfaction (Y). From The results obtained are expected to be the recommendation for the Penajam Paser Utara regency Prosecuting attorney Office to develop a much higher quality of the website, So as to increase the utilization of public services through the Penajam Paser Utara regency Prosecuting Attorney Office website, besides that it is also suggested for the future that the Penajam Paser Utara regency prosecuting Attorney Office is given the attention to the overall of quality of the Penajam Paser Utara Regency Prosecuting Attorney Office website in order to maintain or to increase of the user satisfaction in using their website